Tectonic hazards - Dunn, Cameron; Degg, Martin R. (TSG - Top spec geography, 2012)
Tectonic hazards is as very popular topic at GCSE, post 16 and university level. It enthuses countless numbers of students to study the subject further because of it topicality, relevance and ability to link physical and human geography. This book explores the geography of earthquakes, volcanoes and tsunami, set in the context of disaster trends and human response. The physical processes of plate tectonics are investigated in detail in order to understand the key causes of tectonic hazards and how these often translate into tragic disasters. The book briefly reviews the development of plate tectonic science as well as looking forward to examine the consequences of tectonic hazards in a world of increasing population and risk.